IT governance and IT application orchestration capability role on organization performance during the COVID-19 pandemic: An intervening of business-IT alignment - Afrizal Tahar; Hafiez Sofyani; Detra Putri Kunimasari (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2021)
The COVID-19 pandemic has evolved into a multi-faceted global crisis with massive challenges for any organization around the world. With lockdowns and other social distancing protocols implemented in countries worldwide, economic activities and social interactions become increasingly reliant on technology. This study aimed to examine the intervention role of business-IT alignment on the influence of IT governance (ITG) and IT application orchestration capability (IT-AOC) on organization performances. The educational sector was chosen as an object of study as this sector will experience a decade of radical technology-driven change due to COVID-19's stimulus and there were limited IT-AOC studies that used this sector as a research object. This study use a survey method and purposive sampling with a total classified sample of 55 higher education institutions (HEIs) and 110 respondents involved represent the samples. Data analysis was conducted using a Variance-Based Structural Equation Modeling (VB-SEM) approach of Partial Least Square (PLS) technique. The results suggest that both ITG and IT-AOC have a positive effect on organization performances. Moreover, this study proved that business-IT alignment can intervene the influence of ITG and IT-AOC on organization performances.